Affordable Care Act and Cancer Survivors' Financial Barriers to Care: Analysis of the National Health Interview Survey, 2009-2018. Issue 10 (October 2021) - Su, Christopher T.; Okullo, Dolorence; Hingtgen, Stephanie; Levine, Deborah A.; Goold, Susan D.
Abstract : PURPOSE: Since Affordable Care Act (ACA) implementation in 2014, studies have demonstrated gains in insurance coverage for cancer survivors < 65 years. We assessed the impact of ACA implementation on financial barriers to care by stratifying survivors at age 65 years, when individuals typically become Medicare-eligible. METHODS: We used data from respondents with cancer in the 2009-2018 National Health Interview Survey. We identified 21, 954 respondents representing approximately 7.4 million survivors, who were then age-stratified at age 65 years. Survey responses regarding financial barriers to medical care and medications were analyzed, and age-stratified multivariable logistic regression modeling was performed, which evaluated the impact of ACA implementation on these measures, adjusted for demographic and socioeconomic variables. RESULTS: After multivariable logistic regression, ACA implementation was associated with higher adjusted odds of Medicaid insurance (odds ratio [95% CI] 2.02 [1.72 to 2.36]; P < .0001) and lower adjusted odds of no insurance (0.57 [0.48 to 0.68]; P < .0001). Regarding financial barriers, ACA implementation was associated with lower adjusted odds of inability to afford medications (0.68 [0.59 to 0.79]; P < .0001), inability to afford dental care (0.83 [0.73 to 0.94]; P = .004), and delaying care (0.78 [0.69 to 0.89]; P = .002) in the 18-64 years group. Similarly, ACA implementation was associated with lower adjusted odds of secondary outcomes such as delaying refills, skipping doses, and anxiety over medical bills. Similar associations were not seen in the > 65 years group. CONCLUSION: Survivor-reported measures of financial barriers in cancer survivors age 18-64 years significantly improved following ACA implementation. Similar changes were not seen in the Medicare-eligible cohort, likely because of high Medicare enrollment and few uninsured.